Rat dental pulp tissue reaction after capped with propolis derived nonflavonoid extract - Sabir, Ardo (Universitas Padjadjaran, 2011)
Propolis is a resinous material collected by honey bees from various plants. Many types of research have shown that it has antibacterial and anti-inflammation activities. Flavonoid is the main chemical substance in propolis that inhibits bacterial growth and reduces the release of free radicals, suggesting that this component has anti-bacterial and anti-inflammatory properties. However, there is another chemical substance in propolis that shows antibacterial dan anti-inflammatory activities. The purpose of the present study was to assess the rat dental pulp tissue reaction after capped with propolis derived non-flavonoids extract. Non-flavonoids substances were purified from an ethanol extract of propolis obtained from South Sulawesi, Indonesia. A Class I cavity was prepared on the occlusal surface of the right maxillary first molar in Spraque-Dawley rats. The dental pulp was exposed and then capped with a zinc oxide-based filler as a control (Group I), or non-flavonoids propolis (Group II). Then, each cavity was filled with glass ionomer cement. The animals were sacrificed at week 1, 2, or 4. Biopsy samples were obtained, and these were stained and viewed by light microscopy. The histological examination was based on the presence of polymorph nuclear leukocytes and macrophages. The results showed that pulp inflammation occurred in both groups as early as week 1. However, the inflammation occurred in Group II was relatively milder compared to Group I at all time period. Therefore, present results suggest that application of non-flavonoids propolis extract on rat's dental pulp tissue might inhibit inflammatory process.